1995
DOI: 10.1200/jco.1995.13.5.1152
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel as second and subsequent therapy for metastatic breast cancer: activity independent of prior anthracycline response.

Abstract: Paclitaxel's clinically significant activity against metastatic breast cancer extends to patients with many prior chemotherapy regimens. The lack of impact of prior doxorubicin therapy on the likelihood of subsequent response to paclitaxel suggests an important role for this agent in the treatment of refractory metastatic breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(57 citation statements)
references
References 16 publications
2
55
0
Order By: Relevance
“…The median duration of response (7.6 months), time to progression (4.8 months) and estimated survival (13.0 months) are not very different from the results reported with chemotherapy alone [19]. Similar results have also been reported by other investigators applying the same agents in a salvage regimen with some differences in regards to the intervals of paclitaxel administration (biweekly) and patient's characteristics since one third of them were HER2 positive [25].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The median duration of response (7.6 months), time to progression (4.8 months) and estimated survival (13.0 months) are not very different from the results reported with chemotherapy alone [19]. Similar results have also been reported by other investigators applying the same agents in a salvage regimen with some differences in regards to the intervals of paclitaxel administration (biweekly) and patient's characteristics since one third of them were HER2 positive [25].…”
Section: Discussionsupporting
confidence: 76%
“…Paclitaxel (P) has demonstrated single agent response rates of 35% to 53% even as second or third-line treatment [19]. In addition, bevacizumab (B) combined with several chemotherapeutic agents has shown a synergistic effect that was translated into an increase of the response rate in pretreated patients [10] and an increase of the response rate and progression free survival (PFS) as first-line treatment [11] in MBC.…”
Section: Discussionmentioning
confidence: 99%
“…This alternative schedule of administration is supported by an interesting preclinical rationale (Norton, 1997); in addition, the sequence of Epirubicin followed by Paclitaxel (3-h infusion) is also supported by clinical data showing the partially non crossresistance of the two drugs (Gianni et al, 1995a;Seidman et al, 1995). Our group carried out a multicenter randomised phase III trial testing the safety, activity and efficacy of two different schedules of Epirubicin and Paclitaxel (concurrent vs sequential) in advanced breast cancer patients.…”
mentioning
confidence: 98%
“…Paclitaxel is highly effective for both breast cancer without previous treatment (7) and breast cancer previously treated with anthracycline (8). Findings in a Japanese late phase II study showed the effective rate in metastatic breast cancer patients to be 33.7% (21/62) (9).…”
Section: Introductionmentioning
confidence: 99%